A case of worsening condition of armed forces of ukraine fighter after treatment for chronic non-atrophic gastritis excernsation - Avramenko, A.; Magdenko, A.; Dymo, V. (Journal of Education, Health and Sport, 2024)
A pathogenetic explanation was analyzed and given for the case of deterioration in the condition of a Ukrainian Armed Forces fighter after treatment for an exacerbation of his chronic non-atrophic gastritis. It was found that the treatment was carried out without a complete preliminary examination of the patient and without taking into account the interaction of drugs that were used in the treatment regimen and their effect on Helicobacter pylori infection, which was the reason for the sharp deterioration in the fighter’s condition.